Post all the fan arts! : An animated discussion exploring participatory culture : a thesis presented in partial fulfilment of the requirements for the degree of Masters in Design at Massey University, Wellington, New Zealand - Hackett, Claire (Massey University, 2014)
This animation focused project investigates fandom and, in particular, fan art. Through case study analysis of fan sites, the participant study of fans’ creative practises, and animated argument, the project explores participatory culture from an insider’s perspective.
Keywords: Fan art; Fan culture; Participatory culture; Fandom